Wiretapping As An Instrument For Law Enforcement Of The Crime Of Bribery Through Deponeering For The Sake Of Receiving State Finances - Halawa, Rabani Meryanto; Suwadi, Pujiyono; Hartiwiningsih,; Isharyanto, (BiLD Law Journal, 2022)
This study aims to apply administrative sanctions by making the culprits of bribery who are caught red-handed, pay maximum fines based on the results of wiretapping without serving imprisonment. Based on the observation that prosecutions and court decisions against defendants for bribery offences still focus on imprisonment without optimizing the payment of the maximum fine, from among many sources of state revenue, one originates from the Non-Tax State Revenue (PNBP) sector. This normative type of research possessing a conceptual and statutory approach shows that first, the discretion to stop prosecuting bribery offenses for reasons of state revenue to reduce state expenditures to finance the life of the defendant/convict while in the State Detention Center/Penitentiary and can overcome overcapacity; secondly, increase Non-Tax State Revenue and third, the examination of cases is not protracted by prioritizing the principle of contante justitie (quick, simple and low-cost trial).